Phase-specific differential regulation of mechanical allodynia in a murine model of neuropathic pain by progesterone - Choi, Sheu-Ran; Roh, Dae-Hyun; Moon, Ji-Young; Beitz, Alvin J.; Lee, Jang-Hern (Frontiers in Pharmacology, 2023)
Progesterone has been shown to have neuroprotective capabilities against a wide range of nervous system injuries, however there are negative clinical studies that have failed to demonstrate positive effects of progesterone therapy. Specifically, we looked into whether progesterone receptors or its metabolizing enzymes, cytochrome P450c17 and 5α-reductase, are involved in the effects of progesterone on neuropathic pain after chronic constriction injury (CCI) of the sciatic nerve in mice. Intrathecal progesterone administration during the induction phase of chronic pain enhanced mechanical allodynia development and spinal glial fibrillary acidic protein (GFAP) expression, and this enhancement was inhibited by administration of ketoconazole, a P450c17 inhibitor, but not finasteride, a 5α-reductase inhibitor. Furthermore, phospho-serine levels of P450c17 in the spinal cord were elevated on day 1 after CCI operation, but not on day 17. In contrast, intrathecal progesterone administration during the maintenance phase of chronic pain decreased the acquired pain and elevated GFAP expression; this inhibition was restored by finasteride administration, but not by ketoconazole. The modification of mechanical allodynia brought on by progesterone in CCI mice was unaffected by the administration of mifepristone, a progesterone receptor antagonist. Collectively, these findings imply that progesterone suppresses spinal astrocyte activation via 5α-reductase activity during the maintenance phase of chronic pain and has an analgesic impact on the mechanical allodynia associated with the growing neuropathy. Progesterone, however, stimulates spinal astrocytes during the induction stage of peripheral neuropathy and boosts the allodynic impact caused by CCI through early spinal P450c17 activation.